2005
DOI: 10.1002/jsfa.2378
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two biodegradable coatings on corn silage quality

Abstract: This experiment was performed to assess two different biodegradable coating formulations for the preservation of corn silage quality. Soy-and casein-based biodegradable coatings were evaluated for their ability to exclude oxygen and preserve corn silage. Experiments were conducted under natural conditions outdoors. The effect of the coating composition on silage quality was compared with the quality of silage covered with a plastic (0.15 mm) (positive control) and uncovered (negative control) after 4 and 8 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…Similar relationships were reported by Denoncourt et al (2006), who covered ensiled maize with biodegradable film based on soy protein, calcium caseinate, carboxymethylcellulose, zein and palmitic acid.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Similar relationships were reported by Denoncourt et al (2006), who covered ensiled maize with biodegradable film based on soy protein, calcium caseinate, carboxymethylcellulose, zein and palmitic acid.…”
Section: Resultssupporting
confidence: 82%
“…However, the management of worn-out polyethylene films is a problem. Alarmingly, worn-out silage wrap is going to illegal dumping sites, being buried or burned, while the released components of polymer plastics are a serious environmental threat (Rymarz and Klecan, 2001;Majdiuk, 2002;Rutkowska et al, 2002;Denoncourt et al, 2004aDenoncourt et al, , 2004bŚwiątkowski and Walczak, 2004;Borreani and Tabacco, 2005;Laffin et al, 2005;Denoncourt et al, 2006Denoncourt et al, , 2007Borreani et al, 2014;Borreani and Tabacco, 2015). One alternative to standard coating is biodegradable film produced on the basis of natural origin polymers (chitosan, cellulose, starch, soy or whey protein, and others) or synthetic macromolecular compounds that provide food for microorganisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incineration of the foil causes release of toxic polymeric components (dioxins, furans, phosgene), which poses a serious threat to living organisms (Rymarz and Klecan, 2001;Majdiuk, 2002;Rutkowska et al, 2002;Denoncourt et al, 2006Denoncourt et al, , 2007Gach et al, 2010). Gach et al (2010) report that in Poland, the foil wrapping used in silage production is poorly handled in excess of 70% cases after being used, therefore its components should not be substances harmful to the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Polymers used in the production of biodegradable films are obtained by natural means (chitosan, cellulose, starch, soy or whey protein and others), biotechnological synthesis of macromolecular weight compounds (MMWCs) or by the manufacture of products containing biodegradable fillers or modifiers (natural polymers), possessing their own biodegradability capabilities (Majdiuk, 2002). However, the basic conditions to be met when using biodegradable materials for covering the raw material for the purposed of producing silage, is the effective protection against air (oxygen), maintaining high feed quality during feeding and producing silage that is safe for animal health (Denoncourt et al, 2006(Denoncourt et al, , 2007Gach et al, 2010). The results of the study carried out by Grabowicz et al (2015) showed that the modified, low-density, polyethylene (oxo-biodegradable) foil, similarly to standard foil, protected maize from air access during fermentation and after opening of the tank, and the time of oxo-biodegradation was adjusted to the rate of silage removal from the silo.…”
Section: Introductionmentioning
confidence: 99%